For every real number x, define [x] to be equal to the greatest integer less than or equal to x. (We call this the "floor" of x.) For example, [4.2] = 4, [5.7] = 5, [-3.4]=-4, [0.4... For every real number x, define [x] to be equal to the greatest integer less than or equal to x. (We call this the "floor" of x.) For example, [4.2] = 4, [5.7] = 5, [-3.4]=-4, [0.4] = 0, and [2] = 2. (a) Determine the integer equal to $\lfloor \frac{1}{3} \rfloor + \lfloor \frac{2}{3} \rfloor + \lfloor \frac{3}{3} \rfloor + ... + \lfloor \frac{59}{3} \rfloor + \lfloor \frac{60}{3} \rfloor$. (The sum has 60 terms.) (b) Determine a polynomial p(x) so that for every positive integer m > 4, $\lfloor p(m) \rfloor = \lfloor \frac{1}{3} \rfloor + \lfloor \frac{2}{3} \rfloor + \lfloor \frac{3}{3} \rfloor + ... + \lfloor \frac{m-2}{3} \rfloor + \lfloor \frac{m-1}{3} \rfloor$ (The sum has m - 1 terms.) A polynomial f(x) is an algebraic expression of the form f(x) = $a_nx^n$ + $a_{n-1}x^{n-1}$ + ... + $a_1x + a_0$ for some integer n $\geq$ 0 and for some real numbers $a_n, a_{n-1}, ..., a_1, a_0$.

Question image

Understand the Problem

The question involves the floor function and asks us to evaluate two expressions. Part (a) asks to find the integer value of a sum of floor functions. Part (b) requires determining a polynomial that satisfies a given condition related to a similar sum of floor functions.

Answer

(a) 590 (b) $p(x) = \frac{1}{6}x^2 - \frac{5}{6}x + \frac{2}{3}$
Answer for screen readers

(a) 590 (b) $p(x) = \frac{1}{6}x^2 - \frac{5}{6}x + \frac{2}{3}$

Steps to Solve

  1. Evaluate the floor terms in part (a)

We evaluate the floor of each term in the sum $\lfloor \frac{1}{3} \rfloor + \lfloor \frac{2}{3} \rfloor + \lfloor \frac{3}{3} \rfloor + ... + \lfloor \frac{59}{3} \rfloor + \lfloor \frac{60}{3} \rfloor$.

  1. Group the terms by their floor values

$\lfloor \frac{1}{3} \rfloor = 0, \lfloor \frac{2}{3} \rfloor = 0$. Then $\lfloor \frac{3}{3} \rfloor = 1, \lfloor \frac{4}{3} \rfloor = 1, \lfloor \frac{5}{3} \rfloor = 1$. $\lfloor \frac{6}{3} \rfloor = 2, \lfloor \frac{7}{3} \rfloor = 2, \lfloor \frac{8}{3} \rfloor = 2$. The pattern is that for every increase of 3 in the numerator, the floor increases by 1. We can rewrite our sum, grouping terms, as follows:

$ (\lfloor \frac{1}{3} \rfloor + \lfloor \frac{2}{3} \rfloor) + (\lfloor \frac{3}{3} \rfloor + \lfloor \frac{4}{3} \rfloor + \lfloor \frac{5}{3} \rfloor) + (\lfloor \frac{6}{3} \rfloor + \lfloor \frac{7}{3} \rfloor + \lfloor \frac{8}{3} \rfloor) + ... + (\lfloor \frac{57}{3} \rfloor + \lfloor \frac{58}{3} \rfloor + \lfloor \frac{59}{3} \rfloor) + \lfloor \frac{60}{3} \rfloor$ which simplifies to $ (0 + 0) + (1 + 1 + 1) + (2 + 2 + 2) + ... + (19 + 19 + 19) + 20 $

  1. Calculate the sum in part (a)

We have $2(0) + 3(1) + 3(2) + ... + 3(19) + 20 = 3(1 + 2 + ... + 19) + 20$. The sum of the first n integers is $\frac{n(n+1)}{2}$. Therefore, the sum of integers from 1 to 19 is $\frac{19(20)}{2} = 190$.

Therefore the total sum is $3(190) + 20 = 570 + 20 = 590$.

  1. Evaluate the sum in part (b) for different values of m

We want to find a polymial $p(x)$ such that $\lfloor p(m) \rfloor = \lfloor \frac{1}{3} \rfloor + \lfloor \frac{2}{3} \rfloor + \lfloor \frac{3}{3} \rfloor + ... + \lfloor \frac{m-2}{3} \rfloor + \lfloor \frac{m-1}{3} \rfloor$. Let $S(m) = \lfloor \frac{1}{3} \rfloor + \lfloor \frac{2}{3} \rfloor + \lfloor \frac{3}{3} \rfloor + ... + \lfloor \frac{m-2}{3} \rfloor + \lfloor \frac{m-1}{3} \rfloor$.

If $m = 5$, then $S(5) = \lfloor \frac{1}{3} \rfloor + \lfloor \frac{2}{3} \rfloor + \lfloor \frac{3}{3} \rfloor + \lfloor \frac{4}{3} \rfloor = 0 + 0 + 1 + 1 = 2$. If $m = 6$, then $S(6) = \lfloor \frac{1}{3} \rfloor + \lfloor \frac{2}{3} \rfloor + \lfloor \frac{3}{3} \rfloor + \lfloor \frac{4}{3} \rfloor + \lfloor \frac{5}{3} \rfloor = 0 + 0 + 1 + 1 + 1 = 3$. If $m = 7$, then $S(7) = \lfloor \frac{1}{3} \rfloor + \lfloor \frac{2}{3} \rfloor + \lfloor \frac{3}{3} \rfloor + \lfloor \frac{4}{3} \rfloor + \lfloor \frac{5}{3} \rfloor + \lfloor \frac{6}{3} \rfloor = 0 + 0 + 1 + 1 + 1 + 2 = 5$. If $m = 8$, then $S(8) = \lfloor \frac{1}{3} \rfloor + ... + \lfloor \frac{7}{3} \rfloor = 0 + 0 + 1 + 1 + 1 + 2 + 2 = 7$. If $m = 9$, then $S(9) = \lfloor \frac{1}{3} \rfloor + ... + \lfloor \frac{8}{3} \rfloor = 0 + 0 + 1 + 1 + 1 + 2 + 2 + 2 = 9$. If $m = 10$, then $S(10) = \lfloor \frac{1}{3} \rfloor + ... + \lfloor \frac{9}{3} \rfloor = 0 + 0 + 1 + 1 + 1 + 2 + 2 + 2 + 3 = 12$.

  1. Find a pattern for S(m)

The sums $S(5), S(6), S(7), S(8), S(9), S(10)$ are $2, 3, 5, 7, 9, 12$. These don't seem to have an immediately-obvious polynomial pattern

However, we can think about dividing the $m-1$ terms into groups of 3. There are $\lfloor \frac{m-1}{3} \rfloor$ full groups of 3 terms, which contribute $0 + 1 + 2 + ... + (\lfloor \frac{m-1}{3} \rfloor - 1)$ to the sum. But, each such group of 3 actually contribues $0 + 1 + 2 = 3n$, so $0 + 1 + 2$ is the sum of 3 terms where $i/3$ goes from $n$ to $n + 1 -1/3$. Consider $ \sum_{i=1}^{m-1} \lfloor \frac{i}{3} \rfloor$ We can use the following formula: $\sum_{i=1}^{n} \lfloor \frac{i}{k} \rfloor = \frac{(n \mod k)(n - (n \mod k))}{2k} + \frac{k(N)(N-1)}{2k}$ $N = \lfloor \frac{n}{k} \rfloor$. In our problem, $n = m - 1$ and $k = 3$. $N = \lfloor \frac{m-1}{3} \rfloor$. $\sum_{i=1}^{m-1} \lfloor \frac{i}{3} \rfloor = \frac{(m-1 \mod 3)(m-1 - (m-1 \mod 3))}{2 \times 3} + \frac{3 \lfloor \frac{m-1}{3} \rfloor(\lfloor \frac{m-1}{3} \rfloor - 1)}{2 \times 3} $ $ = \frac{(m-1 \mod 3)(m-1 - (m-1 \mod 3))}{6} + \frac{\lfloor \frac{m-1}{3} \rfloor(\lfloor \frac{m-1}{3} \rfloor - 1)}{2} $ When simplified, yields $\frac{(m-1)(m-4)}{6}$. Since $m>4$, the floor is not needed.

$p(x) = \frac{(x-1)(x-4)}{6} = \frac{x^2 - 5x + 4}{6} = \frac{1}{6}x^2 - \frac{5}{6}x + \frac{2}{3}$.

(a) 590 (b) $p(x) = \frac{1}{6}x^2 - \frac{5}{6}x + \frac{2}{3}$

More Information

For part (a), we grouped the terms such that each group had the same integer value for its floor. We then summed the groups and found that it equals to 590. For part (b), we want to find a polynomial $p(x)$ s.t. $\lfloor p(m) \rfloor = \lfloor \frac{1}{3} \rfloor + \lfloor \frac{2}{3} \rfloor + ... + \lfloor \frac{m-1}{3} \rfloor$. We can use the summation formula to calculate the value, which equals $\frac{(x-1)(x-4)}{6}$, for $x>4$.

Tips

  • For part (a), a common mistake is failing to group terms properly or making a calculation error when summing the groups. Careful arithmetic is needed.
  • For part (b), correctly identifying the polynomial is critical. One may make a mistake by not knowing the formula for summation of a floor function.

AI-generated content may contain errors. Please verify critical information

Thank you for voting!
Use Quizgecko on...
Browser
Browser